Formulation and evaluation of Salbutamol sulphate microspheres by solvent evaporation method - V.V Prasanth, Akashmoy Chakraborty, Sam T Mathew, Rinku Mathappan, V. Kamalakkannan (Journal of Applied Pharmaceutical Science)
Salbutamol sulphate (SS) loaded microspheres were prepared by solvent evaporation method with combination of hydroxy propyl methyl cellulose and Carbopol polymers in various proportions. A total of eleven formulations were prepared i.e. E1, E2, E3, E4, E5, E6, E7, E8, E9, E10 and E11.The particle size of all the formulations were ranged between 110±0.02 and 183±0.02µm. The entrapment efficiency was ranged between 68.3±0.01 and 94.9±0.02%. Based on above parameters four formulations were selected i.e. E5, E8, E9 and E10 for further studies like micromeretic properties, swelling index and in-vitro release profile. It was confirmed with the results of micromeretic property that all the selected formulations showed good flow property. Release data were analyzed based on Highuchi kinetics and Korsmeyer-Peppas equation and all the selected formulations showed good fit to Highuchi model. Stability studies showed almost negligible changes in particle size, entrapment efficiency and drug release throughout the study period.
Keywords: Salbutamol sulphate, swelling index, carr’s index, microspheres, Higuchi kinetics, stability study.